V-doped nickel phosphorus material and preparation method and application thereof

By growing V-NiZn-LDH microsphere arrays on foam nickel conductive substrates and synthesizing V-Nivac2P/NF materials, the problem of catalyst oxygen evolution overpotential in salt water electrolysis is solved, and efficient electrolytic oxygen evolution and hydrogen evolution performance is achieved. And significantly improves the stability of the material.

CN119506934AActive Publication Date: 2025-02-25XINJIANG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411664220.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

During the electrolysis of brine, existing catalysts are prone to overpotential oxygen evolution, resulting in ClER competition reactions and reducing the efficiency of the anode selective OER.

Method used

V-NiZn-LDH microsphere arrays were grown by hydrothermal method on foam nickel conductive substrates and V-Nivac2P/NF materials with rich surface defects were synthesized by selective alkali etching and low-temperature phosphorylation.

Benefits of technology

Excellent performance of electrolytic oxygen and hydrogen evolution in salt water electrolysis was achieved. The OER overpotential was only 330mV and the HER overpotential was only 70mV, and the stability was as high as 2000 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506934A_ABST
    Figure CN119506934A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolyzed water catalysts, and discloses a V-doped nickel phosphorus material as well as a preparation method and application thereof. According to the preparation method, a V-NiZn-LDH microsphere array is uniformly grown on NF through a hydrothermal method, then a precursor with abundant defects is obtained through a selective alkaline etching method, and the ferro-nickel phosphide V-Nivac2P / NF which is anchored on foamed nickel and has abundant surface defects is successfully prepared. In a 1M KOH solution, the prepared V-Nivac2P / NF self-supporting electrode shows excellent water electrolysis oxygen evolution performance and hydrogen evolution performance. An in-situ Raman spectrum shows that in the OER process, the defect obviously accelerates reconstruction from adjacent nickel atoms to a high-activity NiOOH substance, and the high-activity NiOOH substance becomes a real catalytic activity center. DFT calculation also shows that the introduction of vacancies can improve the conductivity of the catalyst, and in the step of adsorbing * OOH, V-Nivac2P / NF can effectively reduce the adsorption energy barrier of * OOH.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic water catalysts, and more specifically relates to a V-doped nickel-phosphorus material and a preparation method and application thereof. Background Art

[0002] Currently, non-renewable fossil fuels such as oil, coal and natural gas account for more than 80% of the global energy supply and dominate carbon dioxide emissions. To ensure long-term sustainability, the use of renewable energy sources such as solar and wind energy to produce green hydrogen by electrolysis of water is widely regarded as the most promising energy carrier for various end-use areas. Commercial water electrolyzers usually require ultra-high purity water as a feedstock to maximize service life and save costs, which is an impractical approach in hot and arid areas where fresh water supply is insufficient. For example, Xinjiang has sufficient photovoltaic and wind power generation potential. Compared with renewable energy and electrolysis, Xinjiang is located inland, and electrolysis of seawater will increase the cost of hydrogen production. Therefore, electrolysis of brackish water provides rich opportunities for areas with limited freshwater resources. Brine electrolysis can be divided into HER and OER, accompanied by competition from anode halide reactions, especially ClER. Therefore, the main challenge of brine electrolysis is how to minimize the overpotential of catalyst oxygen evolution, avoid ClER, and selectively carry out OER at the anode.

[0003] Among many catalysts, transition metal phosphides have attracted much attention due to their unique physicochemical properties, including high conductivity and abundant reserves. However, among many catalysts, transition metal phosphides have attracted much attention due to their unique physicochemical properties, including high conductivity and abundant reserves. Scientists have shown through a large number of experiments that the high HER activity of the Ni2P (001) surface can be attributed to the P-Ni bridge site bonding with the reaction intermediates with moderate strength after combining with P. With the further study of transition metal phosphides, scientists have also developed a series of non-noble and noble, phosphorus-deficient and phosphorus-rich TMPs families with high activity for HER, OER, etc. in recent years. To date, a large number of studies are still focused on developing different preparation methods to obtain different TMPs, or exploring their different applications. Although Ni2P has been developed for hydrogen production, in the face of harsh brine electrolysis, we need to find a suitable strategy to modify it. At present, a large number of studies have greatly improved the catalytic performance of transition metal phosphides through the vacancy introduction strategy. Ionic vacancies can effectively reduce the OER energy barrier of transition metal phosphides to oxyhydroxides, thereby optimizing the binding energy of OER intermediates and enhancing the overall OER kinetics. Combined with the inherent high HER activity of Ni2P, transition metal phosphides can be prepared into efficient bifunctional catalysts.

[0004] Therefore, how to provide a V-doped nickel-phosphorus material and a preparation method and application thereof is a problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies in the prior art, the present invention provides a V-doped nickel-phosphorus material and a preparation method and application thereof, wherein nickel foam is used as a conductive substrate, Zn particles are used as a vacancy producing agent, a precursor with a spherical morphology is in situ grown on the surface of nickel foam by a hydrothermal method, and a micron sphere array V-Ni is synthesized by alkaline etching and low-temperature phosphating. vac 2P / NF.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a V-doped nickel-phosphorus material, characterized in that it comprises the following steps:

[0008] (1) NiCl2·6H2O, Zn(NO3)2·6H2O, VCl3, NH4F and (NH4)2CO were dissolved in deionized water with constant magnetic stirring to form a uniform solution;

[0009] (2) transferring the uniform solution to a stainless steel autoclave lined with polytetrafluoroethylene, adding the pretreated nickel foam, heating for reaction, and then naturally cooling to room temperature, repeatedly washing with deionized water, and vacuum drying at 60° C. to obtain a V-NiZn-LDH / NF precursor;

[0010] (3) The V-NiZn-LDH / NF precursor was immersed in a KOH solution for alkaline etching, the defective products were collected and washed with deionized water and ethanol several times, and dried under vacuum at 60 °C to obtain the defective products;

[0011] (4) The defective product is placed in a porcelain boat on the downstream side of the tube furnace, and NaH2PO2 is added to another porcelain boat on the upstream side. The tube furnace is heated and kept warm in an argon environment, and naturally cooled to room temperature to obtain V-Ni vac 2P / NF material.

[0012] Preferably, the molar ratio of NiCl2·6H2O, Zn(NO3)2·6H2O, VCl3, NH4F, (NH4)2CO and deionized water in step (1) is 1:0.4:0.2:6:5:1.67.

[0013] Preferably, the stirring time in step (1) is 30 min.

[0014] Preferably, the heating temperature in step (2) is 120° C. and the heating time is 8 hours.

[0015] Preferably, the concentration of KOH in step (3) is 6 M, and the alkaline etching time is 6 h.

[0016] Preferably, the mass ratio of the NaH2PO2 in step (4) to the deionized water in step (1) is 0.5:30.

[0017] Preferably, the heating rate of the tubular furnace in step (4) is 2°C / min, the temperature is raised to 350°C, and the insulation time is 2h.

[0018] The present invention also provides a V-doped nickel-phosphorus material prepared by the above method.

[0019] The present invention also provides application of the above-mentioned V-doped nickel-phosphorus material in salt water decomposition.

[0020] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides a V-doped nickel-phosphorus material and a preparation method and application thereof, which have the following beneficial effects:

[0021] (1) The present invention uniformly grows V-NiZn-LDH microsphere arrays on NF by a hydrothermal method, and then obtains a precursor with rich defects by a selective alkaline etching method, and successfully prepares nickel iron phosphide V-Ni with rich surface defects anchored on nickel foam. vac 2P / NF. V-Ni prepared in 1M KOH solution vac The 2P / NF self-supporting electrode exhibits excellent oxygen evolution and hydrogen evolution performance in water electrolysis. The current density is 100 mA cm -2 The OER overpotential is only 330 mV and the stability is up to 2000 h. -2 At a current density of 1.5 Å, the HER overpotential is only 70 mV. In situ Raman spectroscopy shows that during the OER process, defects significantly accelerate the reconstruction of adjacent nickel atoms into highly active NiOOH species, becoming the real catalytic active center. DFT calculations also show that the introduction of vacancies can improve the conductivity of the catalyst. In the step of adsorbing *OOH, V-Ni vac 2P / NF can effectively reduce the adsorption energy barrier of *OOH.

[0022] (2) The electronic interaction between the Zn vacancies and V introduced by the present invention and the introduction of Zn ion vacancies can also accelerate the reconstruction of the catalyst, improve the conductivity of the catalyst, and reduce the adsorption energy barrier from *O to *OOH, thereby improving the intrinsic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0024] Figure 1 V-Ni vac Schematic diagram of the synthesis of 2P / NF.

[0025] Figure 2 XRD diagram, where: (a) V-NiZn-LDH / NF; (b) V-Ni vac 2P / NF; (c) V-Ni vac 2P / NF, V, Zn-Ni2P / NF and V-Ni2P / NF.

[0026] Figure 3 SEM images, including: (a) V-NiZn-LDH / NF; (b) V-Ni vac 2P / NF-1; (c) V-Ni vac 2P / NF, (d)V-Ni vac 2P / NF-2.

[0027] Figure 4 SEM images, where: (a), (b) V, Zn-Ni2P / NF; (c), (d) V-Ni vac 2P / NF; (e), (f) V-Ni2P / NF.

[0028] Figure 5 V-Ni vac Characterization images of 2P / NF, including: (a) TEM image; (b) HRTEM lattice fringes; (c) SAED image; (d) element distribution map.

[0029] Figure 6 (a) is V-Ni vac Total XPS spectra of 2P / NF and V, Zn-Ni2P / NF.

[0030] Figure 6 (b)-(e) are V-Ni vac XPS spectra of 2P / NF, where: (b) Ni 2p; (c) V 2p; (d) Zn 2p; (e) P 2p.

[0031] Figure 6 (f) is V-Ni vac Electron paramagnetic resonance spectra of 2P / NF and V, Zn-Ni2P / NF.

[0032] Figure 7 (a)-(b) are LSV curves of V-Ni2P / NF with different V contents, where: (a) HER; (b) OER.

[0033] Figure 7 (c)-(d) are V-Ni with different Zn contents vac LSV curves of 2P / NF, where: (c) HER; (d) OER.

[0034] Figure 8 (a)-(d) are the OER performances of various materials, including: (a) LSV curve; (b) Tafel; (c) Nyquist; (d) C dl ; (e) V-Ni vac Polarization curves of 2P / NF before and after 5000 CV cycles; (f) V-Ni vac Chronopotentiometry curves of 2P / NF at 2000 h.

[0035] Fig. 9 CV curves at different scan rates during the OER process, where: (a) V-Ni vac 2P / NF; (b) V, Zn-Ni2P / NF; (c) V-Ni2P / NF; (d) V-NiZn-LDH / NF.

[0036] Fig.10 (a)-(d) are the HER performance of each material, where: (a) LSV curve; (b) Tafel; (c) Nyquist; (d) C dl ; (e) V-Ni vac Polarization curves of 2P / NF before and after 5000 CV cycles; (f) V-Ni vac Chronopotentiometry curves of 2P / NF at 1000 h.

[0037] Fig.11 CV curves at different scan rates during HER process, where: (a) V-Ni vac 2P / NF; (b) V, Zn-Ni2P / NF; (c) V-Ni2P / NF; (d) V-NiZn-LDH / NF.

[0038] Fig.12 (a)-(d) are the polarization curve of NFF(V, Na)-P||NFF(V, Na)-P, the amount of H2 and O2 fully hydrolyzed, the chronopotentiometry curve in 1M KOH, and the chronopotentiometry curve in 1M KOH+0.5M NaCl, respectively. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The experimental drugs used in the present invention are shown in Table 1, the experimental instruments used are shown in Table 2, and the material characterization instruments used are shown in Table 3.

[0041] Table 1 Main experimental reagents and gases

[0042]

[0043]

[0044] Table 2 Experimental instruments

[0045]

[0046] Table 3 Instruments and models required for material characterization

[0047]

[0048] Example 1

[0049] The pretreatment method of nickel foam is: add the nickel foam to 3M hydrochloric acid for ultrasonic treatment for half an hour, rinse it twice with deionized water, then put it into deionized water for ultrasonic treatment for half an hour, and finally put it into a beaker containing ethanol for ultrasonic treatment for half an hour, and put the washed nickel foam in a vacuum drying oven overnight.

[0050] A method for preparing a V-doped nickel-phosphorus material, characterized in that it comprises the following steps:

[0051] (1) Dissolve 1 mmol NiCl2·6H2O, 0.4 mmol Zn(NO3)2·6H2O, 0.2 mmol VCl3, 6 mmol NH4F and 5 mmol (NH4)2CO in 30 mL deionized water under constant magnetic stirring for 30 min to form a uniform solution;

[0052] (2) The uniform solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and the pretreated nickel foam of 2 cm*3 cm was added, and the mixture was heated at 120°C for 8 h, and then naturally cooled to room temperature, washed with deionized water for 3 times, and vacuum dried at 60°C to obtain a V-NiZn-LDH / NF precursor;

[0053] (3) The V-NiZn-LDH / NF precursor was immersed in a 6M KOH solution for alkaline etching for 6 h, the defective product was collected and washed with deionized water and ethanol three times respectively, and dried under vacuum at 60°C to obtain the defective product;

[0054] (4) The defective product was placed in a porcelain boat on the downstream side of the tube furnace, and 0.5 g of NaH2PO2 was added to another porcelain boat on the upstream side. The tube furnace was heated to 350°C at a rate of 2°C / min in an argon environment and kept at this temperature for 2 h. The tube furnace was naturally cooled to room temperature to obtain V-Ni vac 2P / NF material.

[0055] Comparative Example 1

[0056] The difference from Example 1 is that the amount of Zn(NO3)2·6H2O used in step (1) is 0.2 mmol. The rest is the same. vac 2P / NF-1 material.

[0057] Comparative Example 2

[0058] The difference from Example 1 is that the amount of Zn(NO3)2·6H2O used in step (1) is 0.6 mmol. The rest is the same. vac 2P / NF-2 material.

[0059] Comparative Example 3

[0060] The difference from Example 1 is that Zn(NO3)2·6H2O is not added in step (1). The rest is the same. V-Ni2P / NF material is obtained.

[0061] Comparative Example 4

[0062] The difference from Example 1 is that the alkaline etching in step (3) is omitted. The rest is the same. V, Zn-Ni2P / NF material is obtained.

[0063] Experiment 1 Characterization Experiment

[0064] Firstly, V-NiZn-LDH microsphere arrays were uniformly grown on NF by a hydrothermal method, and then a V-NiZn-LDH / NF precursor with rich defects was obtained by selective alkaline etching. Finally, V-Ni vac 2P / NF, such as Figure 1 As shown in previous studies, Ni and Zn are both divalent cations, and Zn atoms will occupy the position of Ni atoms. Therefore, Ni atoms close to Zn atoms are more susceptible to corrosion.

[0065] The electrocatalytic performance of the catalyst is closely related to the component content and structure. vac The crystal structures of 2P / NF and a series of comparative samples were analyzed. Figure 2 As shown in a, the precursor can match Ni(OH)2(PDF#01-073-6992) and Zn(OH)2(PDF#00-012-0142) well, and V does not form a phase, indicating that the precursor is V-NiZn-LDH / NF. vac The diffraction peaks of 2P / NF catalyst match well with those of Ni2P ( Figure 2 b), the three strong peaks at 44.5°, 51.8° and 76.3° are attributed to the (111), (200) and (220) crystal planes of NF, respectively. The diffraction peaks at 30.4°, 31.8°, 35.4°, 40.6°, 44.6°, 47.4°, 54.2°, 54.4°, 55.1°, 74.7° and 74.9° 2θ correspond to the (110), (011), (200), (111), (021), (210), (300), (002), (211), (400) and (212) planes of Ni2P (PDF#65-3544), respectively. In addition to the peaks of Ni2P diffraction, there are no additional peaks, indicating that the obtained sample is a V-Ni with rich defects. vac 2P / NF. Figure 2 c. In addition, samples without Zn and without alkali etching were also tested. XRD showed that the phases of V-Ni2P / NF and V, Zn-Ni2P / NF were similar to those of V-Ni vac 2P / NF are similar, indicating that the presence or absence of Zn ions does not affect the composition of the catalyst, but only affects the crystallinity of the substance. The presence of an appropriate amount of Zn ions will increase the crystallinity of the catalyst. It can be seen from the illustration that the peak position shifts to a low angle after alkaline etching of Zn atoms, indicating that the lattice is distorted.

[0066] Using scanning electron microscopy ( Figure 3 ) observed the morphology of V-NiZn-LDH / NF. It can be seen from the figure that the precursor is a "hairy" microsphere structure. The precursor samples with different zinc nitrate contents (0.2mmol, 0.4mmol, 0.6mmol) were phosphated and recorded as V-Ni vac 2P / NF-1, V-Ni vac 2P / NF, V-Ni vac 2P / NF-2. V-Ni vac 2P / NF-1 is a micron ball formed by nanosheets, V-Ni vacTo further prove the morphology of the catalyst, when the amount of Zn increased to 0.6mmol, the size of the microspheres also increased. When no Zn was added, it was found that the morphology of V-Ni2P / NF was similar to that of 0.2mmol Zn, indicating that the morphology of the catalyst without Zn and with a small amount of Zn was microspheres formed by nanosheets ( Figure 4 ); When the Zn content is appropriate, V-Ni vac 2P / NF shows a hollow microsphere array structure and grows uniformly on NF. It is this hollow and rough structure that enables electrolysis to well infiltrate the catalyst, thereby improving the catalytic efficiency.

[0067] The present invention also carries out TEM characterization, such as Figure 5 As shown in a, it can be seen from TEM that V-Ni vac 2P / NF is a hollow microsphere structure, which is also consistent with the SEM image, and its thickness is about 500nm. From the high-resolution TEM (HR-TEM), it can be seen that ( Figure 5 b), the 0.19nm and 0.16nm lattice fringes in the microsphere belong to the (210) and (012) crystal planes of Ni2P (PDF#65-3544). The corresponding selected area electron diffraction (SAED) verifies that V-Ni vac The crystal structure of 2P / NF, where the diffraction rings are associated with the (221) and (111) planes of Ni2P, respectively ( Figure 5 c). ICP (Inductively coupled spectroscopy) showed (Table 4), V-Ni vac 2P / NF can better meet the Ni:P ratio of about 2:1, and after alkaline etching, part of Zn is reacted. 2+ , most of the Zn still exists in V-Ni vac 2P / NF. In addition, Figure 5 As shown in the elemental spectrum in d, they are in V-Ni vac The distribution in 2P / NF is also very uniform, and Zn still exists in it. 2+ , which is consistent with the results of ICP. The above analysis results show that the hollow structure of V-Ni vac 2P / NF microsphere.

[0068] Table 4V-Ni vac Inductively coupled spectroscopy data of 2P / NF and V, Zn-Ni2P / NF

[0069]

[0070] X-ray photoelectron spectroscopy (XPS) measurements were further used to carefully analyze the surface composition and chemical state.vac The overall XPS spectrum of 2P / NF clearly shows the signals of Ni, Zn, V and P elements ( Figure 6 a). From the overall XPS spectrum, it can be seen that after alkaline etching, V-Ni vac The signal peak of Zn in 2P / NF weakened, which means that part of the Zn component has been removed. vac Ni 2p( Figure 6 b) High-resolution XPS spectrum shows typical p-orbital spin-orbit splitting signals. In the Ni2pXPS spectrum, the main peaks at 853.8 and 871.0 eV correspond to Ni-P, and there is a pair of peaks with binding energies of 857.1 and 875.2 eV corresponding to Ni 2p 3 / 2 and 2p 1 / 2 Track, proves Ni 3+ and Ni 2+ There is also a pair of satellite peaks located at. Figure 6 c shows the V-Ni vac High-resolution XPS spectra of Zn 2p in 2P / NF, V, and Zn-Ni2P / NF show that Zn2p appears at 1022.37 and 1045.29 eV. 3 / 2 and Zn 2p 1 / 2 In addition, in addition to the V introduced by VCl3 3+ (515.41 / 522.81eV), V-Ni vac The XPS spectrum of V 2p in 2P / NF shows two pairs of peaks ( Figure 6 d), due to the redox reaction and air contact, the two pairs of peaks belong to the surface oxidized V species, V 4+ (516.77 / 523.80eV) and V 5+ (517.83 / 524.83eV). Figure 6 e is the high-resolution P 2p spectrum of the electrocatalyst, P 2p 3 / 2 and P 2p 1 / 2 The double peaks at 129.62 / 130.77 eV belong to the metal-P of the metal phosphide, while the peak at 133.85 eV belongs to the surface oxidation of the phosphide. According to the above XPS results, the doping of V and the introduction of vacancies effectively optimize its electronic structure and further improve its electrocatalytic activity. Figure 6 f is the electron paramagnetic resonance spectrum of the sample. It can be found that at g = 2.003, an obvious peak appears, and after Zn etching, V-Ni vac The vacancies in 2P / NF are greatly increased.

[0071] Experiment 2: Electrochemical performance experiment

[0072] Electrochemical performance evaluation indicators include:

[0073] (1) Linear sweep voltammetry (LSV)

[0074] The test scan rate is 5mV·s -1 The polarization curve at this time is used to analyze the open circuit potential and overpotential of the catalyst of current and voltage. The smaller the overpotential, the higher the catalytic activity.

[0075] (2) Cyclic voltammetry (CV)

[0076] The test scan rates are 20, 40, 60, 80, and 100 mV·s -1 The electrochemical active surface area (ECSA) of the electrocatalyst was evaluated by calculating the double-layer capacitance of the catalyst in the non-Faraday region from the CV curves.

[0077] (3) Electrochemical impedance spectroscopy (EIS)

[0078] The frequency range of EIS test is 0.01 to 10 5 Hz, AC amplitude is 5mV. Evaluate the speed of catalyst reaction kinetics. EIS test potential is 10mA·cm -2 The corresponding potential.

[0079] (4) Stability test

[0080] Through CV testing, the changes in the LSV curve before and after the cycle are observed. The smaller the change, the better the stability. Through chronopotentiometry, the changes in potential during long-term testing at a fixed current are observed. The smaller the change, the better the durability. In addition, a multi-step chronocurrent step test can be used to compare the degree of change in potential during the rise and fall of different currents. If it is symmetrical, it indicates a good mass transfer process.

[0081] The results are as follows:

[0082] The V-Ni vac Electrocatalytic OER and HER performance of 2P / NF, V, Zn-Ni2P / NF, V-Ni2P / NF and V-NiZn-LDH / NF samples. As controls, Pt / C / NF and RuO2 / NF were also tested as industrial electrocatalysts. The amount of V and Zn was also adjusted to optimize the performance of the catalyst ( Figure 7 ), when V is 0.2mmol and Zn is 0.4mmol, V-Ni vac 2P / NF has the best performance.

[0083] Figure 8a shows the polarization curve of the OER test without iR compensation. In order to avoid the interference of metal ion oxidation reaction on oxygen evolution overpotential, linear sweep voltammetry (LSV) adopted a negative scan from high voltage to low voltage with a scan rate of 5 mV·s -1 The overpotentials are 194 and 330 mV, and the current densities are 10 and 100 mA cm -2 ; When the current density is 10 mA·cm -2 , which is better than similar materials V, Zn-Ni2P / NF (226mV), V-Ni2P / NF (221mV), V-NiZn-LDH / NF (370mV) and commercial RuO2 / NF (222mV) electrocatalysts. vac The overpotential of V2P / NF is significantly lower than that of Zn-Ni2P / NF, indicating that the key to improving the activity of Ni vacancies generated by Zn atoms after alkaline corrosion is to improve the activity of Ni vacancies. Figure 8 In b, V-Ni vac Tafel slope of 2P / NF relative to V, Zn-Ni2P / NF (68.6mV·dec -1 )、V-Ni2P / NF(52.0mV·dec -1 )、V-NiZn-LDH / NF(65.9mV·dec -1 ) shows a lower value of 25.1 mV·dec -1 , showing a faster kinetic process during OER. It is worth noting that this phenomenon is also consistent with the results of electrochemical impedance spectroscopy ( Figure 8 c) V-Ni vac The charge transfer resistance of 2P / NF (4.5Ω) is much smaller than that of V, Zn-Ni2P / NF (6.4Ω), V-Ni2P / NF (7.4Ω), and V-NiZn-LDH / NF (63.1Ω). dl ) is an important signal for evaluating surface active sites. According to the reported calculation method, based on Fig. 9 Calculate V-Ni from the CV results vac 2P / NF C dl The value is 10.6mF·cm -2 ( Figure 8 d), which is superior to other similar materials and shows good OER active site supply capacity. Figure 4-8 As shown in e, V-Ni vac In addition to its excellent catalytic activity, 2P / NF also has good stability. vac The polarization curve of 2P / NF catalyst after 5000 CV cycles is almost the same as that before cycling, indicating that V-Ni vac2P / NF catalyst has good OER stability in alkaline electrolyte. Figure 8 f, at 100 mA cm -2 The OER was tested by chronopotentiometry under the conditions of V-Ni vac The long-term stability of 2P / NF shows that V-Ni vac 2P / NF has good stability for OER, with a voltage retention of 93.6% after 1300 hours of testing.

[0084] Fig.10 a shows the polarization curve of HER test. V-Ni vac The 2P / NF electrocatalyst only needs an overpotential of 102 mV to reach 10 mA cm -2 Its performance is slightly higher than that of commercial Pt / C / NF (47mV), but better than similar materials V, Zn-Ni2P / NF (130mV), V-Ni2P / NF (152mV), V-NiZn-LDH / NF (280mV) and commercial electrocatalysts, showing excellent electrocatalytic performance. Fig.10 bLook, V-Ni vac 2P / NF shows 21.4mV·dec -1 V, Zn-Ni2P / NF (52.8mV·dec -1 )、V-Ni2P / NF(63.1mV·dec -1 )、V-NiZn-LDH / NF(88.6mV·dec -1 ) has a lower Tafel slope, which plays a faster kinetic process. Compared with V, Zn-Ni2P / NF (20.0Ω), V-Ni2P / NF (29.5Ω), and V-NiZn-LDH / NF (230.1Ω), V-Ni vac 2P / NF (18.4Ω) has lower R ct value( Fig.10 c), which is consistent with the results of Tafel slope, further confirming its higher catalytic activity. Fig.11 The CV results in C dl The value is 20.4mF·cm -2 ( Fig.10 d). Fig.10 e shows V-Ni vac Polarization curves of HER of 2P / NF catalyst after 5000 CV cycles. vac The polarization curve of 2P / NF catalyst after 5000 cycles decreased slightly compared with the initial polarization curve, indicating that V-Ni vac2P / NF catalysts have very good HER stability in alkaline electrolytes. Fig.10 f, at 100 mA cm -2 The HER was tested by chronopotentiometry under the conditions of V-Ni vac The long-term stability of 2P / NF shows that V-Ni vac 2P / NF has good stability for HER, with a voltage retention rate of 96.7% after 1000 hours of testing.

[0085] The V-Ni vac Catalytic performance of 2P / NF as a bifunctional self-supporting electrode. The main problem of seawater electrolysis is the competitive CIER of hypochlorite formation in alkaline electrolytes. In addition, ions or microorganisms in seawater can hinder and poison the active sites, resulting in poor catalytic activity. The LSV curve shows ( Fig.12 a), V-Ni vac 2P / NF∥V-Ni vac The performance of 2P / NF pair in 1M KOH and 1MKOH+0.5MNaCl showed no significant change. The 2P / NF pair could drive 10 and 100 mA cm in 1MKOH+0.5MNaCl. -2 The required energy input is lower, 1.42 and 1.64V respectively. Fig.12 As can be seen in the volume change curve of water electrolysis in b, the volume ratio of O2 and H2 is about 1:2. The calculation also confirms that the Faraday efficiency of HER and OER in the water electrolysis process is about 100%. vac 2P / NF∥V-Ni vac The operational stability of the 2P / NF pair when water / simulated seawater is decomposed into two electrolytes. -2 , the catalysts can run stably for more than 1800 hours; in 1M KOH + 0.5M NaCl, the catalysts can run stably for nearly 1000 hours without obvious degradation ( Fig.12 c, d).

[0086] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0087] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a V-doped nickel-phosphorus material, characterized in that: The following steps are involved: (1) NiCl2·6H2O, Zn(NO3)2·6H2O, VCl3, NH4F and (NH4)2CO were dissolved in deionized water with constant magnetic stirring to form a uniform solution; (2) transferring the uniform solution to a stainless steel autoclave lined with polytetrafluoroethylene, adding the pretreated nickel foam, heating for reaction, and then naturally cooling to room temperature, washing with deionized water for 2 to 3 times, and vacuum drying at 60° C. to obtain a V-NiZn-LDH / NF precursor; (3) immersing the V-NiZn-LDH / NF precursor in a KOH solution for alkaline etching, collecting the defective product and washing it with deionized water and ethanol for 2 to 3 times, and drying it under vacuum at 60° C. to obtain the defective product; (4) The defective product is placed in a porcelain boat on the downstream side of the tube furnace, and NaH2PO2 is added to another porcelain boat on the upstream side. The tube furnace is heated and kept warm in an argon environment, and naturally cooled to room temperature to obtain V-Ni vac 2P / NF material.

2. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The molar ratio of NiCl2·6H2O, Zn(NO3)2·6H2O, VCl3, NH4F, (NH4)2CO and deionized water in step (1) is 1:0.4:0.2:6:5:1.

67.

3. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The stirring time in step (1) is 30 min.

4. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The heating temperature in step (2) is 120° C. and the heating time is 8 h.

5. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The concentration of KOH in step (3) is 6M, and the alkaline etching time is 6h.

6. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The mass ratio of NaH2PO2 in step (4) to the deionized water in step (1) is 0.5:

30.

7. The method for preparing a V-doped nickel-phosphorus material according to claim 1, characterized in that: The heating rate of the tubular furnace in step (4) is 2°C / min, the temperature is raised to 350°C, and the insulation time is 2h.

8. A V-doped nickel-phosphorus material prepared according to the method according to any one of claims 1 to 7.

9. Use of the V-doped nickel-phosphorus material according to claim 8 in salt water decomposition.

Citation Information

Patent Citations

  • Copper-zinc compound antibacterial powder synthesizing method and product and application thereof

    CN107810975A

  • Preparation method and application of surface-modified layered bimetal hydroxide electrode material

    CN112058310A

  • Vanadium-doped nickel phosphide material with spherical micron-flower-shaped structure as well as preparation method and application of vanadium-doped nickel phosphide material

    CN117263149A

  • Cation-doped nickel phosphide difunctional self-supporting electrode material, and preparation method and application thereof

    CN118910664A